Seminar media pembelajaran berbasis AI: Meningkatkan efektivitas pembelajaran di MAN Kota Blitar - Zumar, Yogi Ainuz; ’Asyiroh, Nahdliana ’Aisyatul; Al Farabi, Bilqis Tarakanita; Salsabila, Rona Atira (Maliki Interdisciplinary Journal, 2024)
The Articial Intelligence Based Learning Media Seminar for teachers is a work program held by KKM UIN Malang students at MAN Blita City whose aim is to improve teacher skills in an effort to utilize technology in the learning process. This seminar focuses on providing teachers with knowledge and understanding in creating interactive and personalized learning materials, by utilizing various tools and applications based on technology or Artificial Intelligence (AI). This activity also discusses the basic concepts of AI, the ethics of its use, and how to overcome challenges that may arise. The methods used in this activity are direct demonstration methods and lecture methods. Seminar participants shared experiences after delivering material by the resource person, and explored the potential of AI technology to increase the effectiveness of learning in the classroom. As a result, it is hoped that teachers can integrate AI technology creatively and ethically, creating a responsive and innovative learning environment. In conclusion, this seminar is important in preparing a teacher to face the demands of 21st century education and maximize the benefits of AI in the learning process.